'I'm proud of what I achieved; I'm also ashamed of what I done': a soccer coach's tale of sport, status, and criminal behaviour. Issue 5 (19th October 2016) - Cowan, Daryl; Taylor, Ian M.
Abstract: The purpose of this study was to explore the life of John (a pseudonym), a soccer coach working with disadvantaged young people. Six open-ended life history interviews over a ten week period ranging between 45 and 75 min were conducted. John described how soccer was fully entwined with aspects of his former delinquent and criminal lifestyle, including missing school lessons to play soccer, the fusion of soccer and youth violence, and competing in teams with local criminals. On the other hand, a soccer programme for people with limited opportunities helped him leave behind a life of delinquency, gang fighting, and selling drugs. Moreover, he came to understand that soccer could help him satisfy his desire for social recognition and fit with a relational narrative in a more socially legitimate way. This study provides an insight into how soccer was used to thwart a soccer coach's formal criminal lifestyle, and also warns against uncritical assumptions that sport can serve as a panacea for deviant behaviour.